Penegakan Hukum Pidana terhadap Praktek Prostitusi Terselubung pada Panti Pijat Tradisional di Indonesia - Mansyur Naseh Husein; Helvis Helvis (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Traditional massage parlors have changed dramatically. Several traditional massage parlors in Indonesia have been in the spotlight in recent years due to the covert prostitution practices that occur in these places. This practice involves sexual services offered as part of traditional massage services, and it has become a serious problem affecting various aspects of society. The problem discussed is how the practice of covert prostitution in traditional massage parlors in Indonesia cannot be fully criminalized under Articles 296 & 506 of the Criminal Code and how criminal law is enforced against the practice of prostitution in covert massage parlors in Indonesia. The aim of this research is to analyze the practice of covert prostitution in traditional massage parlors in Indonesia which cannot yet be fully criminalized under Articles 296 & 506 of the Criminal Code and analyze criminal law enforcement against the practice of prostitution in covert massage parlors in Indonesia. The theories used in this thesis are law enforcement theory and legal certainty theory. The research method was carried out using a statutory approach which was carried out by examining all laws and regulations relating to the legal issues being handled as well as approaching cases that occurred in the practice of disguised prostitution in massage parlor activities. Problems in the Effectiveness of implementing Articles 296 and 506 of the Criminal Code in law enforcement against prostitution in massage parlors is very dependent on the joint efforts of various parties, availability of resources, and commitment to crack down on this crime consistently and fairly. According to the author, criminal law enforcement against the practice of prostitution in hidden massage parlors in Indonesia currently does not yet have full legal certainty in the application of Articles 296 and 506 of the Criminal Code and related laws. Furthermore, related to the law enforcement factor which is less than optimal, according to the author, the legal system in the crime of prostitution does not work properly, especially related to the legal culture of individual officers who have not made efforts to enforce the law. The suggestions in the research are the need for cooperation between the government, community sponsored organizations (NGO ),child protection institutions and civil society in dealing with the problem of prostitution and improving the legal culture or culture where there must be a mental improvement of government officials and law enforcement officials so that there are no more unscrupulous individuals playing in law enforcement efforts against hidden massage parlors under the guise of prostitution.